PARTISIPASI MASYARAKAT DALAM PROSES PENGAWASAN ANGGARAN DANA DESA (ADD) (Studi Kasus di Desa Kuma Selatan Kecamatan Essang Selatan Kabupaten Kepulauan Talaud) - Paradenti, Ekasary; Kawung, Evelin J. R.; Zakarias, Jhon D. (HOLISTIK, Journal Of Social and Culture, 2017)
Permendagri No. 113 stated that Village Budget is all the rights and obligations which can be valued with money and goods involved with implementation of villageâ€™s rights and obligations. Budget control is the whole activities included:, planning, implementing, administration, reporting and accountability process of the village budget.Alokasi Dana Desa (Village Budgeting) or so called â€œADDâ€ is the balancing fund from APBD after special allocation fund is reduced. The budgeting needs control from the society, it has to be clear, transparent and accountable therefore understandable for every part of the society in the village.This research aims to 1.) Know the role of the society to Village Budget Controlling process (ADD) in Desa Kuma Selatan kecamatan Essang Selatan. 2) Get description about the utilization of the Village Budget involved in Village Development.The method used in this research is qualitative method while analysis data technique used Miles and Huberman (2001) method. The research showed that the role of the society in village budget controlling process is still far from expectation. This happened because the knowledge of the control itself. Controlling process is to prevent leakage, irrelevance implementation and position abuse. In facts, the controlling of village budget process is consistent with supervision function, and therefore divided into two parts, intern and extern controlling. Intern controlling or supervision can be applied through the implementation of project for Dinas PU as the decision maker in every development. Intern controlling also involved with implementation of ADD by the leader of the organization in the village itself therefore the leader have role and right to implement intern controlling process. While the extern controlling involved with the society.Â Keywords: Role of society, controlling, supervision, ADD